True Atomic-Scale Imaging in Three Dimensions: A Review of the Rebirth of Field-Ion Microscopy. (24th March 2017) - Vurpillot, Francois; Danoix, Frédéric; Gilbert, Matthieu; Koelling, Sebastian; Dagan, Michal; Seidman, David N.
Abstract: This article reviews recent advances utilizing field-ion microscopy (FIM) to extract atomic-scale three-dimensional images of materials. This capability is not new, as the first atomic-scale reconstructions of features utilizing FIM were demonstrated decades ago. The rise of atom probe tomography, and the application of this latter technique in place of FIM has unfortunately severely limited further FIM development. Currently, the ubiquitous availability of extensive computing power makes it possible to treat and reconstruct FIM data digitally and this development allows the image sequences obtained utilizing FIM to be extremely valuable for many material science and engineering applications. This article demonstrates different applications of these capabilities, focusing on its use in physical metallurgy and semiconductor science and technology.